2001
DOI: 10.1001/archinte.161.17.2133
|View full text |Cite
|
Sign up to set email alerts
|

Obese Patients' Perceptions of Treatment Outcomes and the Factors That Influence Them

Abstract: These data signal a therapeutic dilemma in which the amount of weight loss produced by the best behavioral and/or pharmacologic treatments is viewed as even less than disappointing. Patients with the highest pretreatment weights are likely to have the most unrealistic expectations for success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
117
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(136 citation statements)
references
References 27 publications
19
117
0
Order By: Relevance
“…As shown in previous studies, 2,3 we found that women, younger participants and those with a higher BMI expected and desired greater reductions. The finding that Hispanic participants had greater weight loss expectations and goals was surprising.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As shown in previous studies, 2,3 we found that women, younger participants and those with a higher BMI expected and desired greater reductions. The finding that Hispanic participants had greater weight loss expectations and goals was surprising.…”
Section: Discussionsupporting
confidence: 86%
“…[1][2][3][4][5] The losses they expected after 1 year of behavioral 19,20 There was a small positive relationship between participants' expected and achieved weight losses at week 26. Thus, participants with higher expectations lost more weight in the first 6 months of treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…7,17 Although monotherapy treatment in clinical studies with various anorexigenic agents, whether small molecules or peptide hormone therapeutics, can significantly reduce weight, the overall magnitude of weight loss tends to be modest, plateauing in the single-digit range. 18 These modest effects have been attributed, in part, to the redundancy of feeding pathways. Combining agents with different anorexigenic mechanisms, such as a small molecule and a peptide hormone, may help mitigate some of the redundancies and facilitate additive reductions in food intake and body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of different programme has mainly focused on the patients' weight loss expectations and the results have indicated that the expectations are mostly unrealistic; more so for women than men (Foster et al, 1997;Foster et al, 2001;Linne et al, 2002).…”
mentioning
confidence: 99%